Expressão gênica diferencial do feijoeiro (Phaseolus vulgaris L) durante interação com a raça 65 de Colletotrichum lindemuthianum - Silva, Caroline Marcela da (2019)
Knowing the transcriptional profile of genotypes under specific treatments has been considered as a tool of great relevance for the molecular understanding of the patossystems, illuminating the knowledge of resistance. The anthracnose caused by the fungus Colletotricum lindemuthianum is one of the most important diseases that affects the bean crop, which can cause significant losses in production under conditions favorable to the pathogen. The objective of this work was to: (i) investigate by RT-qPCR, in contrasting genotypes for resistance to race 65 of Colletotricum lindemuthianum, the level of expression of genes previously selected in the literature, for their probable association with the response of resistance to anthracnose, and (ii) to verify, by the cDNA-RAPD technique, the existence of variability of expression and to obtain information about the transcriptome of susceptible and anthracnose resistant cultivars when inoculated by the pathogen. Among the analyzed genes, PVPOD, CBP, MAPKK and PGIA presented differential expression between the inoculated treatments and the control of the lineages, offering information on the resistance pathways in this pathological system. The use of the RAPD technique in express material allowed the amplification of 1,619 bands in 251 loci, about 50% of them being polymorphic, attesting to the existence of variability of gene expression, with the identification of putative loci of interest, through qualitative and quantitative differences observed between inoculated and uninoculated treatments of both lines, showing variation in the gene regulation according to the applied stimulus.